Rainwater Processing System into Ready-to-Drink Water PIR Sensor (Hc-Sr501) and Arduino Uno - Mushthofa, Mushthofa; Indriani, Yulia; Yanwar, Amanda Pradhani (Universitas Diponegoro, 2025)
Lack of drinking water is a condition where the availability of clean water is insufficient to meet basic human needs. This study aims to build a rainwater treatment system based on the Passive Infrared (PIR) HC-SR501 sensor and the Arduino Uno device. The method used is the applied experimental method. The results of the study showed that the content of rainwater seen from the physical, chemical and biological properties after the filtration process was as follows: temperature 27.4 ° C, total dissolved solids (TDS) 163 mg/l, turbidity 1.31 NTU, color 0 TCU -> 0 TCU, odorless, pH 8.1, nitrate (as NO3) 0.7 mg/l, nitrate (as NO2) 0.12 mg/l, Chromium Valence 6 (Cr6+) 0 mg/l, Iron (Fe) 0.61 mg/l, Manganese (Mn) 0.03 mg/l, Chlorine Residue 0 mg/l, Arsenic (As) not detected, Cadmium (Cd) 0.060 mg/l, Lead (Pb) 0.06 mg/l, Fluoride (F) 0 mg/l, Aluminum 0.05 mg/l, Total Coliform 4 CFU/100ml, E.coli 0 CFU/100ml. This data shows that rainwater has changed from not drinkable to drinkable although there are some shortcomings that require modification, namely in the Ultraviolet lamp. The modified filtration treatment design can optimize the physical, chemical, and biological properties of the air.